Uluslararası hukukta kuvvet kullanma ve Birleşmiş Milletler barışı koruma harekatları ile egemenlik - Velibeyoğlu, Cahit (My University, 2005)
FORCE PROJECTION IN INTERNATIONAL LAW AND SOVEREIGNTY BY MEANS OF UNITED NATIONS PEACE SUPPORT OPERATIONS In the threshold of a new era, starting from early 1900's all nations began to appear dependent on each other in an ever-accelerating global world where the concept of classical total sovereignty transitions itself into a new understanding discribed as partial soverignty, especially by financial means.Threats, today are described mainly at economical level but yet not succesfully resolved without use of force projection. After devastating centuries of wars and conflict all around the globe, nations found themselves in a common urge to unite under the flag of International Organizations in the hope of ensuring a safe platform to negotiate over conflicting subjects and find solutions at political level , thus, preventing the painfull history repeat it self again. United Nations (U.N.) is inarguably the most widespread of all international organizations with the participation of almost evey country as amember. This dissertation aims to examine how U.N. finds legal grounds to interfere with governmental issues and under what circumstances U.N. resolutions affect national sovvereignty. Althought the unity is suppossed to be founded upon existence of equal members, U.N. unfortunately has acted more like an oligarchical club so far.This situation brings a lot of criticism especially about the special rights and authority of five permanant members of the Security Concil. It is a fact that thronghout decades, many conflicts have arisen in deffrent parts of the global map just because these privileged members used their authority in favour of their foreign policies. It is also this fact why U.N. today can be described anything but thrustworthy, apart from the motives of its foundation. In the recess period of its existence, reliability lost can only be attained by a well-performed renovation Project in the political structure and authority dispersal equally spread members of the union

ULUSLARARASI HUKUKTA KUVVET KULLANMA VE BİRLEŞMİŞ MİLLETLER BARIŞI KORUMA HAREKATLARI İLE EGEMENLİK 20. Yüzyıl başlarından itibaren Klasik Egemenlik anlayışı artık yerini sınırlı egemenlik anlayışına bırakmıştır. Küreselleşme ile şekillenen yeni dünya düzeninde artık tüm devletler birbirlerine muhtaç duruma gelmişlerdir. Yeni dünya düzeninde tehditler daha çok ekonomik düzeydedir. Ancak devletlerin birbirlerine karşı kuvvet kullanmaları engellenememiştir. Muhtemelen bundan sonrada engellenemeyecektir. Dünyanın artık tek isteği barış ve huzur içinde yaşamaktır. Devletler barış ve huzur içinde yaşamak ve geçmişte yaşanan acıların tekrarını önlemek maksadıyla uluslararası örgütler kurma yoluna gitmişlerdir. Yüzyılımızın bu anlamda en etkin örgütü olarak Birleşmiş Milletler kurulmuştur. Bu gün hemen hemen bütün devletler bu örgüte üye durumundadır.Bu çalışmamızda Birleşmiş Milletler Örgütünün devletin egemenliğine hangi nedenlerle müdahale edebildiği anlatılmıştır. Günümüzde özellikle Birleşmiş Milletler Örgütü devletin egemenliğine İnsani amaçlarla müdahale etmektedir. Kendisine ait bir askeri gücü olmayıp, üye devletlerin gönüllü yardımlarıyla oluşturulan Birleşmiş Milletler maalesef büyük devletlerin güdümü altındadır. Haklı olarak bugünkü yapısı eleştirilmektedir. Bu eleştirilerin büyük bir bölümü Güvenlik Konseyinin beş daimi üyesinin statüsü ve bunların veto yetkileri ile ilgilidir. Bu devletler veto yetkilerini hep kendi ülkelerinin dış politikaları yönümde kullanmışlardır. Bu yönden de dünyanın birçok yerinde çatışmalar devam etmektedir. Bu durum Birleşmiş Milletlerin güvenirliğini zayıflatmıştır. Birleşmiş Milletler Örgütünü, devletlerin gerçek anlamda eşit olarak söz sahibi olduğu yapıya kavuşturmak zorunlu bir hal almıştır. Ancak bu durumda Birleşmiş Milletler güvenilir bir örgüt olabilir.
Keywords: Barış; Birleşmiş Milletler; Birleşmiş Milletler Barışı Koruma Harekatları; Egemenlik